Indikator gender untuk perencanaan pembangunan : pengalaman Repelita VI. - Indonesia. Badan Perencanaan Pembangunan Nasional (Jakarta : Badan Perencanaan Pembangunan Nasional bekerjasama dengan Women's Support Project II, CIDA, 2001)
Gender analysis pathway, gender indicators for policy of planning and development in Indonesia.
"Lampiran matriks indikator"--P. [97]-230.
"Juni 2001."
Includes bibliographical references (p. 95-96).
Mode of access: Internet.
Keywords: Women -- Indonesia -- Social conditions; Regional planning -- Indonesia; Sex role -- Government policy -- Indonesia; Social prediction -- Indonesia; Social indicators -- Indonesia; Women in development -- Indonesia